Teori ASyA (Adaptive Sharī‘ah Advantage): Kajian Interdisipliner tentang Maqāṣid al-Sharī‘ah dan Konsep MILES dalam Merumuskan Ketahanan Masyarakat Muslim - Liddinillah, M Yakhsyallah (Pascasarjana UIN ANTASARI Banjarmasin, 2025)
Contemporary Muslim societies are increasingly shaped by a pattern of ritual-centered religiosity that emphasizes symbolic devotion while neglecting the substantive objectives of Islamic law (maqāṣid al-sharī‘ah). This trend has generated a fragile form of social resilience, marked by weakened critical literacy, poor economic planning, deteriorating family communication, and vulnerability to psychological and social pressures. The situation represents an urgent crisis of meaning, where religious enthusiasm is no longer balanced by strategic rationality and ethical responsibility. Classical Islamic scholarship, represented by al-Ghazālī, al-Shāṭibī, and Ibn al-Qayyim, positions maqāṣid al-sharī‘ah as the heart of Islamic law, oriented toward the preservation of religion, life, intellect, wealth, and lineage. However, in contemporary contexts, this normative framework often remains abstract and detached from practical social realities, creating a gap between theory and lived experience. This study aims to formulate the ASyA (Adaptive Sharī‘ah Advantage) Theory as an integrative model that reconnects maqāṣid al-sharī‘ah with the practical dimensions of modern life through the MILES framework (Money, Intelligence, Location, Education, Status). The study employs an original qualitative framework called the Maqāṣid–MILES Adaptive Synthesis Method (MMAS), which consists of three stages: (1) textual deconstruction of classical maqāṣid literature, (2) logical fallacy mapping of contemporary religious discourse, and (3) critical adaptive synthesis linking maqāṣid domains with the MILES components. The research produces an interdisciplinary conceptual matrix in which each element of MILES is mapped onto the five essential protections of maqāṣid al-sharī‘ah. This integration offers a dynamic and contextualized model capable of strengthening religious integrity, economic resilience, intellectual maturity, environmental awareness, and intergenerational continuity in Muslim communities.The ASyA Theory presents a transformative approach that shifts maqāṣid from a purely normative framework into an operational strategy for social resilience. It is recommended as a foundational model for future empirical research, educational reform, and policy-oriented Islamic social development.